Serologic evidence of West Nile virus infection in horses, Coahuila State, Mexico - Blitvich, Bradley J.; Fernández Salas, Ildefonso; Contreras Cordero, Juan Francisco; Marlenee, Nicole L.; González Rojas, José Ignacio; Komar, Nicholas; Gubler, Duane J.; Calisher, Charles; Beaty, Barry J. (National Center for Infectious Diseases, Centers for Disease Control and Prevention (CDC), 2003)
Serum samples were obtained from 24 horses in the State of Coahuila, Mexico, in December 2002. Antibodies to West Nile virus were detected by epitope-blocking enzyme-linked immunosorbent assay and confirmed by plaque reduction neutralization test in 15 (62.5%) horses. We report the first West Nile virus activity in northern Mexico.